A Comparative Study of Thermal Impact on Erbium Doped Distributed Feedback Fiber Laser Output Power - Jian Guo; Haifeng Qi; Zhiqiang Song; Jiasheng Ni; Chang Wang; Weitao Wang; Gangding Peng (IEEE Photonics Journal, 2020)
The temperature dependency of erbium doped distributed feedback fiber laser output performance is experimentally and theoretically investigated with two major pump schemes. The output power declined linearly as temperature increased from 30 °C to 120 °C for 980 nm and 1480 nm pumped test laser while the later exhibited stronger heat susceptibility. Further experiment and analysis identified the temperature induced absorption and emission cross section variation at pump and signal wavelength together with population inversion rate difference are the originations of the thermal sensitivity discrepancy between the two pump setups. Associated theoretical simulation concludes the erbium doped distributed feedback fiber laser thermal output sensitivity is dependent on its gain dynamics and grating structure simultaneously.